PART TIME JOB AND ITS EFFECTS ON UNIVERSITY STUDENTS: A CASE OF UNIVERSITY STUDENTS IN VIETNAM - Huynh Tan Hoi, Nguyen Tan Danh (Chelonian Research Foundation, 2023)
Nowadays, it is common for students to work part-time to cover their lives and earn extra income and student in Ho Chi Minh city is no exception. However, part-time jobs will affect the student's living and learning process. Besides, there is also an opinion that when working part-time, students will learn more experience than in school. Therefore, this article aims to study the influence of part-time work on outcomes. student learning outcomes. Methodology: The article was completed based on a comparison of current and previous studies. By using Likert scale, the article compares opinions and finds results and finds suitable solutions. Results: This study shows that there is a difference in learning outcomes through actual surveys of two students in FPT University who have part-time jobs and don't work part-time. Research has found the effects of part-time jobs, which are the factors that make students' academic performance decrease. Conclusions: From those bases, the research has proposed solutions and recommendations to help FPT University students get a part-time job to improve their study results.